2020
DOI: 10.1088/2053-1591/ab8094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Y/Zn ratio on microstructure and properties of as-extruded Mg-Y-Zn alloys

Abstract: In this work, four Mg-Y-Zn alloys with specific Y/Zn (wt%) ratio have been prepared. The effects of Y/Zn (wt%) on the microstructure of extruded Mg-Y-Zn alloy were investigated by SEM and TEM. The mechanical properties and corrosion behavior of extruded Mg-Y-Zn alloy were also studied by tensile test, electrochemical and immersion measurements. The corrosion mechanism was studied by SEM observation of the surface morphology of the samples after immersion corrosion. The result indicates that the as-extruded Mg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The reported hybrids of AgNWs and silk‐based structures apply spray‐ or dip‐coating processes and they are mainly focused on the formation of conductive layers. There have been also applied various functionalization techniques to bond metal nanostructures and silk‐based materials using linkers, such as hyperbranched polymers to coat silk fabric with attapulgite nanoparticles 16 or polydopamine to immobilize covalently SF on the titanium implant surface 17 . The direct feeding of silkworms with AgNWs resulted in obtaining reinforced properties of silk fibers 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The reported hybrids of AgNWs and silk‐based structures apply spray‐ or dip‐coating processes and they are mainly focused on the formation of conductive layers. There have been also applied various functionalization techniques to bond metal nanostructures and silk‐based materials using linkers, such as hyperbranched polymers to coat silk fabric with attapulgite nanoparticles 16 or polydopamine to immobilize covalently SF on the titanium implant surface 17 . The direct feeding of silkworms with AgNWs resulted in obtaining reinforced properties of silk fibers 18 .…”
Section: Introductionmentioning
confidence: 99%
“…There might be two reasons for the grain refinement. On the one hand, the addition of Sr increased the degree of subcooling of the alloys and elevated the nucleation rate of the primary α-Mg phase, and refined the grain structures [13,14]. On the other hand, an increase of the Sr content increased the growth limiting factor (GRF).…”
Section: As-cast Microstructuresmentioning
confidence: 99%
“…Previous studies have shown that mechanical harvesting based on resonance-vibration technology is an efficient technique that can improve harvesting efficiency and reduce costs [10][11][12]. At present, the primary research focus has been on the effect of the vibration method and vibration parameters on fruit drop rate and fruit damage rate [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%